Prediction and Prevention of Type 1 Diabetes - Primavera, Marina; Giannini, Cosimo; Chiarelli, Francesco (Frontiers in Endocrinology, 2020)
Type 1 Diabetes (T1D) is one of the most relevant chronic autoimmune diseases in children. The disease is characterized by the destruction of beta cells leading to hyperglycemia and to a lifelong insulin-dependent state. Although several studies in the last decades have added relevant key component elements, the complex pathogenesis of the disease is not yet completely understood. Recent studies have been focused on several factors, including family history and genetic predisposition (HLA and non-HLA genes) as well as environmental and metabolic biomarkers, with the aim of predicting the development and progression of T1D. Once a child becomes symptomatic, the residual beta cell mass has already reached a critical threshold (usually a residual of 20-30% of normal), thus representing the very late phase of the disease. In particular, this final stage follows two previous asymptomatic stages, which have been precisely characterized. According to the long natural history and complex pathogenesis of the disease, prevention strategies might be postulated in three major options: primary, secondary and tertiary prevention. To date, the primary prevention is carried out through the very early stage before the development of beta cell autoimmunity through vaccines or by modifying microbiota-induced immune-regulation. In addition, the availability of novel humoral and metabolic biomarkers able to characterize subjects at high risk of progression, have allowed to postulate secondary and tertiary prevention strategies aimed to preserve residual beta cell destruction and/or to prolong the remission phase after the onset of T1D. This review focuses on the major current knowledge on prediction and prevention of T1D in children.